The Effect of Leadership Style, Motivation and Work Discipline on Employee Performance at PT. Kilang Kecap Angsa - Jessy Lim; Andre Fitriano; Agusman Derita Gea (Journal of Research in Business, Economics, and Education, 2022)
This study aims to determine the effect of leadership style on employee performance at PT. Kilang Kecap Angsa, knowing the effect of work motivation on employee performance at PT. Kilang Kecap Angsa, knowing the effect of work discipline on employee performance at PT. Kilang Kecap Angsa and to know the influence of leadership style, work motivation and work discipline simultaneously on the performance of employees at PT. Kilang Kecap Angsa. This research is a quantitative description research using a questionnaire instrument carried out with a total population of all employees of PT. Kilang Kecap Angsa involved 314 people using the slovin formula sampling technique, so a sample of 75 people was obtained. The results of the study partially obtained the value of the t statistic coefficient of leadership style is 2,317 and a t table value of 1,992 where t statistic > t table (2,317 > 1,992) with a sig value <0.05 (0.023 <0.05), the t statistic coefficient value of work motivation is 3,656 and the t table value is 1,992, where t statistic > t table (3,656 > 1,992) with a sig value <0.05 (0,000 <0.05), the t statistic coefficient value of work discipline is 8,035 and the t table value is 1,992 where t statistic > t table (8,035 > 1,992) with a sig value <0,05 (0,000 <0, 05). Furthermore, simultaneously the F statistic value of the variable Leadership style, work motivation and work discipline are 71,736 F table value of 2,493 where F statistic > F table (71,736 > 2,493) with a sig value <0.05 (0.000 <0.05). The adjusted RSquare value is 0.741 or adjusted R2 x 100% of 74.10%, meaning that the research independent variables make a very large contribution in explaining employee performance by 74.10% while the remaining 25.90% is influenced by other factors.